2018
DOI: 10.1038/s41557-018-0061-4
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional Na–Cl crystals of unconventional stoichiometries on graphene surface from dilute solution at ambient conditions

Abstract: NaCl in a 1:1 stoichiometry is the only known stable form of the Na-Cl crystal under ambient conditions, and non-1:1 Na-Cl species can only form under extreme conditions, such as high pressures. Here we report the direct observation, under ambient conditions, of NaCl and NaCl as two-dimensional (2D) Na-Cl crystals, together with regular NaCl, on reduced graphene oxide membranes and on the surfaces of natural graphite powders from salt solutions far below the saturated concentration. Molecular dynamics and dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 32 publications
6
117
1
Order By: Relevance
“…2D, nonstoichiometric Na 2 Cl and Na 3 Cl crystals were observed on the surfaces of reduced graphene oxide (rGO) membranes and natural graphite powders under ambient conditions, as shown in Figure 6b. [ 84 ] The results were further confirmed by theoretical studies using molecular dynamics and DFT calculations, indicating that the strong Na + –π interactions at the cation‐graphite surfaces accounted for the unconventional crystallization process. The strong interactions and charge transfer between Na + and the π system resulted in the excessive adsorption of Na + to form Na‐Cl crystals of nonstoichiometry.…”
Section: Other Typical Applications Of Cation–π Interactions In Graphmentioning
confidence: 70%
See 1 more Smart Citation
“…2D, nonstoichiometric Na 2 Cl and Na 3 Cl crystals were observed on the surfaces of reduced graphene oxide (rGO) membranes and natural graphite powders under ambient conditions, as shown in Figure 6b. [ 84 ] The results were further confirmed by theoretical studies using molecular dynamics and DFT calculations, indicating that the strong Na + –π interactions at the cation‐graphite surfaces accounted for the unconventional crystallization process. The strong interactions and charge transfer between Na + and the π system resulted in the excessive adsorption of Na + to form Na‐Cl crystals of nonstoichiometry.…”
Section: Other Typical Applications Of Cation–π Interactions In Graphmentioning
confidence: 70%
“…b) Reproduced with permission. [ 84 ] Copyright 2018, Springer Nature. c) Schematic diagram showing that the ionic liquid guides the in situ growth of TiO 2 ‐B nanosheets on CNTs.…”
Section: Other Typical Applications Of Cation–π Interactions In Graphmentioning
confidence: 99%
“…The oxygen‐containing groups on rGO NSs induced strong adsorption of the precursors into the interlayer space of rGO, which facilitated the nucleation and growth of MoS 2 NSs in such a confined environment. More recently, Fang and co‐workers found that the 2D NaCl crystals with unconventional stoichiometries (i.e., Na 2 Cl and Na 3 Cl) can be obtained in the interlayer region of rGO (Figure 2c) 60. The formation of 2D NaCl crystals was confirmed by X‐ray diffraction (XRD), from which a new Bragg peak at ≈32° is observed (Figure 2d).…”
Section: D Nanostructured Materials Based On Confined Synthesismentioning
confidence: 86%
“…d) XRD patterns of 2D NaCl crystals and corresponding control samples. Reproduced with permission 60. Copyright 2018, Nature Publishing Group.…”
Section: D Nanostructured Materials Based On Confined Synthesismentioning
confidence: 99%
“…GO displays an extensive prospect in fields such as nanofiltration [23,24], gas separation [25,26], forward osmosis [27], PV [28][29][30][31][32], ion sieving etc. [33][34][35][36][37]. Although CG was widely applied in semiconductors [38,39], supercapacitors [40], electrochemiluminescence [41], biosensors [42][43][44], and hydrogels [45], less literature is available on its application in membrane separation comparing with GO.…”
Section: Introductionmentioning
confidence: 99%